A case report of locally invasive Aspergillus fumigatus infection in a patient on canakinumab. Issue 3 (4th September 2018) - Chandrakumaran, Anchalia; Malik, Manpreet; Stevens, Michael P; Abbate, Antonio
Abstract: Background: Canakinumab is a human monoclonal interleukin-1 antibody that has been studied in the Canakinumab Anti-Inflammatory Thrombosis Outcome Study (CANTOS) trial and shown to prevent recurrent cardiovascular events, while increasing the incidence of neutropenia and risk of severe infections. Case summary: This is a case report of a locally invasive aspergillus infection in a patient with uncontrolled diabetes mellitus who was receiving canakinumab for 3.5 years as part of the CANTOS trial. He presented with headaches and left eye pain and was found to have a large left ethmoid sinus mass extending into the orbit on computed tomography scan of the head. Cultures from an endoscopic biopsy of left ethmoid sinus grew Aspergillus fumigatus . Canakinumab was discontinued, and he was discharged on voriconazole with improvement in his headaches and left eye pain. Discussion: The anti-inflammatory properties of canakinumab could have blunted the patient's immune response allowing the mycetoma to invade adjacent tissue. If canakinumab was approved for the secondary prevention of cardiovascular events then it is important to be cognizant of its potential to delay the presentation of any infection.